Understanding writing blocks - Hjortshoj, Keith (Oxford University Press, 2001)
This book demystifies the causes of writing blocks, which are often ignored, misunderstood, or attributed to obscure psychological disorders. Hjortshoj examines blocks instead as real writing problems arising from specific misconceptions, writing behaviors, and rhetorical factors present at different stages of the writing process. In a lively and informative style, he defines the nature of writing blocks, examines their causes, and offers advanced undergraduates, graduate students, and professional writers the diagnostic tools and strategies necessary for getting their work done